I "media industry studies" in Italia: nuove prospettive sul passato e sul presente dell’industria cine-televisiva italiana (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This issue investigates the current state and possible developments ofMedia Industry Studies in Italy.  Through multiple perspectives andresearch methodologies, it offers insights on the changing role ofItalian public service broadcasting, on the network relations andmodes of production of Italian cinema in the 1950s and 1960s, and onthe challenges posed by the contemporary media landscape.